Isolamento e caracterização de uma lectina e de um inibidor de proteases em sementes de Caesalpinia pulcherrima Linn. - Braga, Renata Chastinet (2006)
Caesalpinia pulcherrima, a small tree known, as "f~amboianzinho", "flaboiant mirim", "barba de barata" ou "brado de estudante" is wildly used in many countries as popular medicine, showing many properties as emmenagogue, antihemorrhagic and abortifacients, and in the treatment of infections. Many studies were done using their several vegetative parts (stems, roots, bark) but few were done with their seeds. These were concentrated in the endospermic polysaccharides. As the leguminous seeds are important sources of proteins, in this paper the isolation and partial characterization of two biologically important cotyledonary proteins: a protease inhibitor and a lectin. The C. pulcherrima protease inhibitor (IniCPTI) was isolated by size exclusion chromatography on Superdex 75 HR, followed by ion exchange chromatography on monoQ column It is a serine protease inhibitor with an apparent molecular mass of 20.9 kDa and shows activity against trypsin and chymotrypsin, showing with trypsin a Ka of 1,92 x 104 and Kd of 3,03 x 10-5, by plasmon surface resonance. It shows 18 % of alfa helix, 30 % of beta sheets and 52 % of other contributions. The CD spectra showed structural changes above 60 °C indicating a low thermal stability. These characteristics suggest that IniCPTI may be classified of the Kunitz type. A galactose-binding lectin was also isolated from the C. pulcherrima cotyledons (CaeLec), bay affinity chromatography on a matrix prepared with cross-linked endospermic galactomannan isolated from the same seeds. The capacity of the lectin to interact with these galactomannans may suggest that, although located in different tissues, these proteins may be in contact during germination and may play a regulation role in the lectin exudation to the soil. Sy affinty chromatography on different matrices, it was shown that CaeLec shows no anomeric specificity, interacting both with alfa and beta linked-galactose oligomers. CaeLec shows a higher activity at the pH 5, loosing all the activity at ph higher than 6. The behavior of the CaeLec stabilty could not be avaliated by CD due to its high content (62%) in randon structure. CaeLec shows better affinity by complex than by simple sugars. CaeLec shows uncommon characteristcs for a legume lectin, as the high randon secondary structure and the higher activity at pH 5.0. More detailed study may be done trying to better understanding of its biological role and applications.